Sosialisasi Dan Edukasi Aplikasi Classpoint Bagi Guru Pada Kurikulum Merdeka Belajar Sekolah Dasar : Indonesia - hevitria, hevitria; Arrosyad, Muhammad Iqbal; Tohir, Muhamad; Adilliyah, Adilliyah; Pratiwi, Saskia (Jurnal Abdimas Madani dan Lestari (JAMALI), 2024)
Community service with a beginner community service scheme carries out outreach activities regarding Classpointi application training for teachers in the independent elementary school learning curriculum. This service is motivated by the lack of ability of STKIP MBB elementary school teachers in using interactive applications to deal with the independent learning curriculum. Therefore, socialization and education activities on the Classpoint application were held for teachers in the independent elementary school learning curriculum. The solution carried out in this service is through the initial observation stage or situation analysis regarding the teacher's understanding and abilities towards interactive applications, the service planning stage, the service implementation stage in the form of classpoint application training for teachers in the independent learning curriculum, precisely implemented at STKIP MBB Elementary School, Pangkalan Baru District, Regency Central Bangka, and the evaluation stage took the form of question and answer activities and guided exercises. The results of community service with socialization and educational activities on the Classpoint application for teachers in the independent primary school learning curriculum can be described in detail according to the stages that have been implemented. These stages include, 1) needs assessment; 2) presentation of material; 3) mentoring; and 4) evaluation.